SUBALKALINE PICROBASALTS AND PLATEAU BASALTS FROM PUTORANA PLATEAU (SIBERIAN CFB PROVINCE). II. MELT INCLUSION CHEMISTRY, COMPOSITION OF "PRIMARY" MAGMAS AND P-T REGIME AT THE BASE OF SUPERPLUME - Ryabchikpv I.D.; Solovova I.P.; Ntaflos T.; Büchl A.; Tikhonenkov P.I. (My University, 2001)
We report the data for melt and fluid inclusions from phenocrysts of subalkaline picrite basalts and tholeiitic plateau basalts from Putorana plateau, Siberian trap province. The analyses of reheated melt inclusions from the investigated rocks show, that the magmas of subalkaline picrite basalts from Putorana plateau were significantly enriched in moderately incompatible (Ti, P) and highly incompatible (K) elements, whereas their concentrations in tholeiitic flood basalts are similar to MORB (with the exception of K). Volatile components played substantial role in the magmas of subalkaline picrite basalts, as is evidenced by the finding of fluid inclusions containing liquid CO2 in the olivine phenocrysts, presence of amphiboles and phlogopites as daughter minerals in melt inclusions and in the matrix of the rocks, saturation of early melts with respect to molten sulfide phases, and by elevated fluorine contents (0.15-0.35 wt%) in the reheated melts quenched into glasses. This confirms Siberian basaltic volcanism as a possible contributor to the mass extinction at the Permian Triassic boundary. The variation of the compositions of reheated melt inclusions from phenocrysts of subalkaline picrite basalts show distinct olivine control even after the recalculation of their compositions to equilibrium with olivine of fertile mantle Iherzolites; this must be due to the loss of normative olivine from primary melts either because of the re-equilibration with the host olivine after the entrapment of melts by growing crystals, or because of the interaction with the minerals of mantle peridotites during the ascend of the originally produced partial melts through the intergranular space of surrounding mantle rocks. The recalculated compositions of reheated melt inclusions from subalkaline picrite basalts with the maximum normative olivine are similar to near-solidus melts in fertile mantle Iherzolites at pressures close to 7 GPa corresponding to potential temperature of ~270° above that for MORB-generating systems; this confirms that the origin of Siberian traps was related to the ascend of hot material from the inner zones of the Earth. Subalkaline picrite basalts from Putorana plateau are not the primary magmas for less magnesian tholeiitic flood basalts from the same locality, but rather they formed from a portion of melt generated at the base of extensive melting column mixed together in the crustal magma chamber with the prevailing volume of more depleted instantaneous melts from the overlying levels of the same column.
Keywords: Triassic; Permian; Палеозой::Пермская; Paleozoic::Permian; Mesozoic::Triassic; Мезозой::Триасовая